2021
DOI: 10.3390/rs13234860
|View full text |Cite
|
Sign up to set email alerts
|

Lithological Mapping Based on Fully Convolutional Network and Multi-Source Geological Data

Abstract: Deep learning algorithms have found numerous applications in the field of geological mapping to assist in mineral exploration and benefit from capabilities such as high-dimensional feature learning and processing through multi-layer networks. However, there are two challenges associated with identifying geological features using deep learning methods. On the one hand, a single type of data resource cannot diagnose the characteristics of all geological units; on the other hand, deep learning models are commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 52 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Upon examining Table 8, our schemes outperform other works in terms of number of parameters and size on disk. Additionally, our work achieved a comparable classification accuracy to the work in [1,41,42], with exceptionally low memory footprint and parameters making it applicable in real-time systems. The closest model in [3] achieved a low accuracy of 81.33% with almost 2.5 the number of parameters used in our work.…”
Section: Cnn Models Training and Evaluationmentioning
confidence: 67%
“…Upon examining Table 8, our schemes outperform other works in terms of number of parameters and size on disk. Additionally, our work achieved a comparable classification accuracy to the work in [1,41,42], with exceptionally low memory footprint and parameters making it applicable in real-time systems. The closest model in [3] achieved a low accuracy of 81.33% with almost 2.5 the number of parameters used in our work.…”
Section: Cnn Models Training and Evaluationmentioning
confidence: 67%
“…Methods based on DL predominantly approach the task of geological element interpretation from the perspective of semantic segmentation. Liu et al [37] proposed a framework that combined multi-source data fusion techniques with a fully convolutional network (FCN) model to enhance the accuracy of geological mapping. The results showcased the framework's efficacy in accurately identifying geological features, including lithological units.…”
Section: Related Workmentioning
confidence: 99%
“…In this respect, Shirmard et al demonstrated that integrating CNNs with ASTER data from southeastern Iran yielded higher-quality geological mapping results than traditional ML techniques [32]. Wang et al constructed a fully convolutional network based on semantic segmentation to interpret rock units by exploring the relationships between diverse data sources [33]. In addition, Han et al introduced an adaptive multisource data fusion network that adaptively extracted and fused multiscale deep-rock information features using atrous spatial pyramid pooling (ASPP) operations and attention blocks [34].…”
Section: Introductionmentioning
confidence: 99%